Effects of Training Methods and Achievement Motivation on Badminton Skills - Ashadi Cahyadi; Ade Rahmat; Agi Ginanjar (Universitas Pendidikan Indonesia, 2023)
The purpose of this study was to determine the effect of training methods and achievement motivation on badminton skills. The method used in this study was an experimental research method with a factorial design. Participants of this study were 28 badminton athletes chosen using a systematic sampling technique. The instruments used were the badminton games performance test and achievement motivation questionnaire. Data analysis techniques used statistical descriptions, the two-way ANOVA test, and the Tukey test. The results of the study concluded that there was an effect of training methods and achievement motivation on badminton playing skills. It is suggested that further research is conducted by involving more participants, thus the results can be more generalized.